Stock Return: What Are The Determinants? - Abel Tasman; Marwan Marwan; Nurzahra Suardi (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2019)
Investment is one of the ways to save wealth in the long term. In order to get the return, investors can invest in the capital market . This study aimed to examine the effect of dividend policy and funding decision on the stock return with the firm value as an intervening variable in property, real estate, and building construction companies which listed in the Indonesian Stock Exchange in 2013-2016. In this research the dividend policy was measured by dividend yield, funding decision was measured by debt to equity ratio, and the firm value was measured by price earning ratio. This study used path analysis with 124 company-year observations. The results of this study show that (1) dividend policy has a negative and no significant effect on the firm value,(2) funding decision has a positive and significant effect on the firm value,(3) dividend policy has a positive and no significant effect on the stock return, (4) funding decision has a positive and significant effect o the stock return, (5) firm value has a positive and significant effect o the stock return. It can be concluded that the determinants of stock return of property, real estate and building construction companies in Indonesia Stock Exchange are funding decision and firm value.